A Scoping Review on the Therapeutic Potential of Resin From the Species Larix decidua Mill. [Pinaceae] to Treat Ulcerating Wounds - Batista, João V. C.; Uecker, Annekathrin; Holandino, Carla; Boylan, Fabio; Maier, Jakob; Huwyler, Jörg; Baumgartner, Stephan (Frontiers in Pharmacology, 2022)
Malignant ulcerating wounds or neoplastic lesions are a considerable burden for patients suffering from advanced cancer. These wounds have no effective treatment and are very difficult to manage. The present review summarizes evidence in support of a hypothesis put forward in anthroposophical medicine, which suggests a beneficial role of resin from the species Larix decidua Mill. [Pinaceae] for treating such wounds. A systematic search strategy was performed using the databases PubMed, EMBASE and SciFinder. The included publications described the chemical composition of this species, as well as in vitro, in vivo and ex vivo experiments using plant extracts and isolated compounds. The results show that among the phytochemical classes, terpenoids were the major components of this species, especially in the resin. The summarized biological experiments revealed antimicrobial, antioxidant and anti-inflammatory effects, with promising potential for the extracts and isolated compounds. However, the molecular mechanisms and toxicological effects are as of yet not conclusively evaluated. From the data of our study, we can conclude that L. decidua might indeed have a promising potential for the treatment of malignant wounds, but definitive information that can prove its effectiveness is still lacking. We therefore suggest that future efforts should be dedicated to the evaluation of L. decidua resin´s therapeutic applications due to its antiseptic action and possibly wound healing properties.